(untitled) (El-Wahat Journal for Research and Studies, 2025)
One of the main contentions in modern applied research is the recognition of learners’ deviated production in second language as being errors or mistakes. This categorisation is built upon the premise that the former represents problems with the learner’s knowledge, i.e., competence, of the second language whereas the latter are local to performance. Determining whether a deviated production is local to competence or performance is achieved by means of frequency. Frequently occurring errors are judged as being errors while less frequently occurring ones are considered as mistakes. This categorisation feeds into subsequent pedagogical decisions, particularly feedback and corrective intervention strategies. In the present study, it is shown that such a categorisation is over-simplistic and can be problematic at times Keywords: Errors; Mistakes, Second Language Learning, Corrective Feedback